First records of Thrips hawaiiensis (Morgan, 1913) and Scirtothrips dorsalis Hood, 1919 (Thysanoptera: Thripidae) in Russia - S.V. Poushkova (Кавказский энтомологический бюллетень, 2020)
Thrips hawaiiensis (Morgan, 1913) and Scirtothrips dorsalis Hood, 1919 (Thysanoptera: Thripidae) are recorded for the fauna of Russia (Krasnodar Region: Sochi, Adler) for the first time. Geographical distribution and morphological characteristics of these two species are given. The possible acclimatization and subsequent formation of a stable and fast growing population of Thrips hawaiiensis on the Black Sea coast is analyzed on the basis of its biological characteristics. Thrips hawaiiensis was found on different plants during the entire period of our observations (March – November 2019), reaching the highest number in summer and autumn. In total, 151 specimens of this species were collected from the following plants: Acacia dealbata Link, Ageratum houstonianum Mill., Azalea L., Bougainvillea glabra Choisy, Camellia japonica L., Chrysantemum × morifolium Ramat., Cinnamomum camphora (L.) J. Presl, Eriobotria japonica (Thunb.) Lindl., Jasminum L., Loropetalum chinense (R.Br.) Oliv., Nerium oleander L., Magnolia grandiflora L., Magnolia stellata (Siebold & Zucc.) Maxim., Ilex aquifolium L., Passiflora caerulea L., Prunus laurocerasus L., Rosa L., Tagetes erecta L., Viola tricolor L., Weigela florida (Bunge) A. DC. Further monitoring in the Black Sea coast of Krasnodar Region is necessary to confirm the naturalization of Scirtothrips dorsalis considering its potential economic threat.